Sauerbruch y Hutton : Contra el tipo - Betsky, Aaron (2003)
Comentario crítico sobre la arquitectura del estudio
Keywords: SAUERBRUCH, MATTHÍAS; HUTTON, LOUISA; YOUNG, LUCAS; LUDLOFF, JENS; SAUERBRUCH HUTTON ARCHITECTS; ARQUITECTURA; TEORIA; CRITICA